ANALISIS PENGARUH BRAND PERSONALITY TERHADAP BRAND AWARENESS DAN PERCEIVED QUALITY DALAM KEPUTUSAN PEMBELIAN KARTU PROVIDER XL DI KOTA PEKANBARU - Siregar, Yan Karda (Jurnal Tepak Manajemen Bisnis, 2015)
The rapid use of smartphones contributed to growing number of Internet subscribers in Indonesia. In 2013, internet users in Indonesia was 35million, 65% of the user used smartphones. XL provider as an internet serv ice provider inIndonesia is one of the biggest and oldest operator after Telkomsel and Indosat. The purposeof this research is to determine the brand personality of XL provider on brand awareness andperceived quality on purchase decision of XL card provider in Pekanbaru city185questionaires were distributed to XL provider users who used this brand for about 6 months inPekanbaru by using snowball sampling method to spread the questionnaire, and then usingSmart PLS as a data analysis tool. The findings suggest that the results of the brandpersonality affects brand awareness and perceived quality significantly. Furthermore, brandawareness and perceived quality affected the purchasing decision significantly, then thepersonality of the brand does not significantly influence the purchase decision. In the indirecttest, brand personality influence purchasing decisions through brand awareness and perceivedquality..Keywords: brand personality, brand awareness, perceived quality, purchase decision.